Comparison of health- related quality of life between obese women with binge eating disorder and obese women without binge eating disorder - Azari, Sheida; Abdolmanafi, Atefe; Zeinodini, Zahra; Poursharifi, Hamid (International Journal of Applied Behavioral Sciences, 2017)
Nowadays obesity It is an important factor in onset of disease and early mortality followed by personal and social consequences. One of the effects of the obesity is its impacts on quality of individual’s life while some studies proved that Binge eating disorder affects obesity consequences. So in this cross sectional study, among all of clients to obesity clinic Sina Hospital with sampling health- related quality of life61 obese women with binge eating disorder was compared with those of 74obese women withoutbinge eating disorder through performing sf-36 questionnaire and the results were analyzed by using independent t-test. Results showed that in six subscales of health-related Quality of Life, the group of women without binge eating disorder ranked over those women with binge eating disorder. Parallel to weight loss in obese and overweight people and due to its impacts on the consequences over the obese people, it seems necessary to equally focus on the treatment of binge eating disorder simultaneously.